Engineered IgG1-Fc Molecules Define Valency Control of Cell Surface Fcγ Receptor Inhibition and Activation in Endosomes - Bailey, Elizabeth M.; Choudhury, Amit; Vuppula, Harika; Ortiz, Daniel F.; Schaeck, John; Manning, Anthony M.; Bosques, Carlos J.; Hoppe, Adam D. (Frontiers in Immunology, 2021)
The inhibition of Fcγ receptors (FcγR) is an attractive strategy for treating diseases driven by IgG immune complexes (IC). Previously, we demonstrated that an engineered tri-valent arrangement of IgG1 Fc domains (SIF1) potently inhibited FcγR activation by IC, whereas a penta-valent Fc molecule (PentX) activated FcγR, potentially mimicking ICs and leading to Syk phosphorylation. Thus, a precise balance exists between the number of engaged FcγRs for inhibition versus activation. Here, we demonstrate that Fc valency differentially controls FcγR activation and inhibition within distinct subcellular compartments. Large Fc multimer clusters consisting of 5-50 Fc domains predominately recruited Syk-mScarlet to patches on the plasma membrane, whereas PentX exclusively recruited Syk-mScarlet to endosomes in human monocytic cell line (THP-1 cells). In contrast, SIF1, similar to monomeric Fc, spent longer periods docked to FcγRs on the plasma membrane and did not accumulate and recruit Syk-mScarlet within large endosomes. Single particle tracking (SPT) of fluorescent engineered Fc molecules and Syk-mScarlet at the plasma membrane imaged by total internal reflection fluorescence microscopy (SPT-TIRF), revealed that Syk-mScarlet sampled the plasma membrane was not recruited to FcγR docked with any of the engineered Fc molecules at the plasma membrane. Furthermore, the motions of FcγRs docked with recombinant Fc (rFc), SIF1 or PentX, displayed similar motions with D 0.15 μm2/s, indicating that SIF1 and PentX did not induce reorganization or microclustering of FcγRs beyond the ligating valency. Multicolor SPT-TIRF and brightness analysis of docked rFc, SIF1 and PentX also indicated that FcγRs were not pre-assembled into clusters. Taken together, activation on the plasma membrane requires assembly of more than 5 FcγRs. Unlike rFc or SIF1, PentX accumulated Syk-mScarlet on endosomes indicating that the threshold for FcγR activation on endosomes is lower than on the plasma membrane. We conclude that the inhibitory effects of SIF1 are mediated by stabilizing a ligated and inactive FcγR on the plasma membrane. Thus, FcγR inhibition can be achieved by low valency ligation with SIF1 that behaves similarly to FcγR docked with monomeric IgG.